Alternate Polyelectrolyte Coating of Chitosan Beads for Extending Drug Release - A. Srinatha; Jayanta K. Pandit (My University)
In the present study, we addressed the factors modifying ciprofloxacin release from multiple coated beads. Beads were prepared by simple ionic cross-linking with sodium tripolyphoshate and coated with alginate and/or chitosan to prepare single, double, or multilayered beads. The water uptake capacity depended on the nature of beads (coated or uncoated) and pH of test medium. The number of coatings given to the beads influenced ciprofloxacin release rate. The coating significantly decreased the drug release from the beads in comparison to uncoated beads (p < 0.001). When the beads were given three coatings, viz., alginate, chitosan, and again alginate, the drug release appeared to follow the pattern exhibited by colon-targeted drug delivery systems with time dependent release behavior. The increase in coating formed a barrier for easy ingress of dissolution medium into the bead matrix, reducing the diffusion of drug. Copyright © Informa Healthcare USA, Inc.
Keywords: Chitosan Beads, Ciprofloxacin, Sodium Alginate, Polyelectrolyte Complex, Single Layered, Multilayered